Reversal of aging‐related emotional memory deficits by norepinephrine via regulating the stability of surface AMPA receptors. Issue 2 (7th January 2015) - Luo, Yi; Zhou, Jun; Li, Ming‐Xing; Wu, Peng‐Fei; Hu, Zhuang‐Li; Ni, Lan; Jin, You; Chen, Jian‐Guo; Wang, Fang
Summary Aging‐related emotional memory deficit is a well‐known complication in Alzheimer's disease and normal aging. However, little is known about its molecular mechanism. To address this issue, we examined the role of norepinephrine (NE) and its relevant drug desipramine in the regulation of hippocampal long‐term potentiation (LTP), surface expression of AMPA receptor, and associative fear memory in rats. We found that there was a defective regulation of NE content and AMPA receptor trafficking during fear conditioning, which were accompanied by impaired emotional memory and LTP in aged rats. Furthermore, we also found that the exogenous upregulation of NE ameliorated the impairment of LTP and emotional memory via enhancing AMPA receptor trafficking in aged rats, and the downregulation of NE impaired LTP in adult rats. Finally, acute treatment with NE or desipramine rescued the impaired emotional memory in aged rats. These results imply a pivotal role for NE in synaptic plasticity and associative fear memory in aging rats and suggest that desipramine is a potential candidate for treating aging‐related emotional memory deficit.